2004
DOI: 10.1292/jvms.66.295
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Autoantibody in Cerebrospinal Fluids from Dogs with Various CNS Diseases

Abstract: ABSTRACT. To examine the prevalence of autoantibody in canine cerebrospinal fluids (CSFs), CSFs were collected from 14 healthy controls and 88 clinical cases with various diseases in the central nervous system (CNS), and were analyzed by an indirect fluoresc ence antibody test on frozen sections of the cerebrum from normal Beagle dogs. An anti-astrocyte autoantibody was detected in 31 clinica l cases with titers ranging from 1:1 to ≥1:100. All tested cases with necrotizing meningoencephalitis (NME: n=22) and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 16 publications
1
70
0
Order By: Relevance
“…The present study was designed to identify the autoantigen for anti-astrocyte autoantibodies, which were frequently detected in the CSF from NME cases [12]. All of the present 9 cases also possessed anti-astrocyte autoantibodies, which were detected by an IFA test on frozen sections of the normal canine cerebrum (data not shown).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The present study was designed to identify the autoantigen for anti-astrocyte autoantibodies, which were frequently detected in the CSF from NME cases [12]. All of the present 9 cases also possessed anti-astrocyte autoantibodies, which were detected by an IFA test on frozen sections of the normal canine cerebrum (data not shown).…”
Section: Discussionmentioning
confidence: 77%
“…Histopathology of NME is characterized by lymphocytic inflammation and subsequent necrosis in the cerebral cortex [20]. While the pathogenesis of NME is unclear, Uchida et al [22] and our previous report [12] demonstrated that dogs with NME possessed anti-astrocyte autoantibodies in their cerebrospinal fluids (CSFs), suggesting that NME is an autoimmune disease. In addition, Suzuki et al [20] reported the immunoglobulin and complement deposition on astrocytes in an NME case, supporting the pathological roles of anti-astrocyte autoantibodies.…”
mentioning
confidence: 97%
“…CSF analysis conducted in our dog showed similar findings. Matsuki et al indicated that the CSF in dogs with necrotizing encephalitis (NME) or GME was strongly positive for anti-GFAP autoantibody [13]. In our dog too, the CSF distemper IP antibody titer was slightly elevated (reference value: CSF level/serum level < 200), although the results of the distemper antigen test were negative.…”
mentioning
confidence: 50%
“…GME mainly develops in the cerebrum, brain stem, cerebellum, and spinal cord, although it can also develop in the eyes [9]. The definitive diagnosis of GME is made by histopathological examination although several studies have revealed that imaging procedures such as magnetic resonance imaging (MRI) and computed tomography (CT), and cerebrospinal fluid (CSF) antibody tests assist in the clinical diagnosis [12,13,21].…”
mentioning
confidence: 99%
“…Granulomatous meningoencephalitis (GME) is a delayed-type, T-cell dependent allergic response in the brain tissue [22]. Additionally, necrotizing meningoencephalitis (NME) is an autoimmune disease that affects brain tissue [13,25,27]. Thus, a highly correlated diagnostic marker is needed to correctly diagnose the various forms and progression of encephalitic disease in the clinic.…”
mentioning
confidence: 99%